Trading favors? UN Security Council membership and subnational favoritism in aid recipients - Maria Perrotta Berlin; Raj M. Desai; Anders Olofsgård (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2022)
We test the hypothesis that aid recipient governments are better able to utilize aid flows for political favoritism during periods in which they are of geo-strategic value to major donors. We examine the effect of a country's (non-permanent) membership on the United Nations Security Council (UNSC) on the subnational distribution of World Bank aid. Specifically, we analyze whether World Bank projects are targeted to regions in which the head of state was born, or to regions dominated by the same ethnic group as that of the head of the state. We find that all regions of a recipient country, on average, receive a greater number of aid projects during UNSC membership years. Moreover, a leader's co-ethnic regions (but not birth regions) receive significantly more World Bank projects and loan commitments during UNSC membership years compared to other years. This effect is driven chiefly by interest bearing loans from the International Bank for Reconstruction and Development (IBRD). Most importantly, we find stronger subnational political bias in aid allocation for aid recipients whose UNSC votes are fully aligned with those of the United States, indicating that exchanges of aid for favors occur in multilateral settings.
Keywords: D30; 330; Aid Recipients; UN Security Council Membership; World Bank aid; aid allocation